H syndrome: Clinical, histological and genetic investigation in Tunisian patients. Issue 8 (29th May 2018) - Jaouadi, Hager; Zaouak, Anissa; Sellami, Khadija; Messaoud, Olfa; Chargui, Mariem; Hammami, Houda; Jones, Meriem; Jouini, Raja; Chadli Debbiche, Achraf; Chraiet, Karima; Fenniche, Sami; Mrad, Ridha; et al.
Abstract: H syndrome is a rare autosomal recessive disorder with characteristic dermatological findings consisting of hyperpigmentation and hypertrichosis patches mainly located on the inner thighs and multisystemic involvement including hepatosplenomegaly, hearing loss, heart abnormalities and hypogonadism. The aim of this study was to conduct a clinical and genetic investigation in five unrelated Tunisian patients with suspected H syndrome. Hence, genetic analysis of the SLC29A3 gene was performed for four patients with a clinical diagnosis of H syndrome. We identified a novel frame‐shift mutation in the SLC29A3 gene in a female patient with a severe clinical presentation. Furthermore, we report two mutations previously described, the p.R363Q mutation in a male patient and the p.P324L mutation in two patients of different age and sex. This paper extends the mutation spectrum of H syndrome by reporting a novel frame‐shift mutation, the p.S15Pfs*86 in exon 2 of SLC29A3 gene and emphasizes the relevance of genetic testing for its considerable implications in early diagnosis and clinical management.